Outcomes Following Chronic Obstructive Pulmonary Disease Presentations to Emergency Departments in Alberta: A Population-Based Study - Brian H Rowe; Donald C Voaklander; Thomas J Marrie; Ambikaipakan Senthilselvan; Terry P Klassen; Rhonda J Rosychuk (Canadian Respiratory Journal)
INTRODUCTION: Chronic obstructive pulmonary disease (COPD) is a complex, multisystem disorder that often results in exacerbations requiring emergency department (ED) management. Following an exacerbation and discharge from the ED, reassessment and management adjustment with a health care provider are recommended to re-establish control of the disease.